Survey and Experimentation: Critical Review of Research Design in Social Sciences - Nafisa Mayukh; Haekal Adha Al-Giffari (CV. Syntax Corporation Indonesia, 2023)
This comparative critical review study delves into the utilization of survey and experimental research designs within the intricate landscape of social sciences. Through a comprehensive analysis of six articles—three for each methodology—focuses on social media's impact on self-esteem (survey) and news consumption effects (experiment). The study's comparative framework critically evaluates the alignment of research designs with objectives, robustness of methodologies, and inherent strengths and weaknesses. It demonstrates how these methodologies, though distinct, offer complementary tools for comprehending complex social phenomena Accordingly, the survey-based investigations emphasize the critical understanding of the interplay between social media use and self-esteem, particularly among the youth. Simultaneously, experimental studies unravel factors shaping news consumption patterns, holding significance for news organizations and researchers seeking to enhance audience engagement. Limitations include sample size constraints and potential bias. Nevertheless, through examination of the research designs and specific contexts, the study underscores the importance of methodological choice and its impact on outcomes. It highlights the potential of innovative techniques like the Experience Sampling Method in surveys and the importance of controlled settings in experiments. These insights further enrich the social sciences' understanding of multifaceted societal dynamics